Wound temperature profiles of coaxial mini‐incision versus sleeveless microincision phacoemulsification. (10th November 2016) - Belkin, Avner; Abulafia, Adi; Michaeli, Adi; Ofir, Shay; Assia, Ehud I
Abstract: Background: Temperature profiles at the corneal wound of coaxial mini‐incision (2.4 mm) cataract surgery and sleeveless microincision (1.1 mm) cataract surgery were compared. Design: Prospective, controlled, paired‐eye clinical trial conducted in a tertiary care hospital. Participants: Twenty patients with mild‐to‐moderate bilateral nuclear sclerotic cataract. Methods: Twenty patients underwent bilateral cataract surgery within a 1‐month period. One eye was operated on by conventional coaxial mini‐incision (2.4 mm) phacoemulsification. The second eye underwent microincision surgery by using a naked phacoemulsification tip and a specialized 19‐gauge anterior chamber maintainer as the sole fluid source (three‐port microincision cataract surgery technique). Patients had moderate bilateral cataracts with no other anterior segment pathology. Temperature at the corneal wound was constantly recorded by using infrared thermal imaging. Main Outcome Measures: Temperatures at the corneal wound. Results: Mean temperatures at the corneal surgical wound were not significantly different between the coaxial and sleeveless groups (31.1 °C ± 2.3 vs . 31.0 °C ± 2. 0; P  = 0.89). There was also no difference in maximum temperatures reached during phaco‐emulsification. Temperatures did not rise above 40 °C during any surgery, and there were no corneal burns. Final visual acuity and intraoperative and postoperative complication rates were similar between the two groups. Conclusions: The temperature profile at the surgical wound using a microincisional sleeveless phacoemulsification technique is comparable with that of the conventional coaxial mini‐incision method.